THE EFFECT OF NEARPOD INTERACTIVE MEDIA IN THE DISCOVERY LEARNINMODEL ON THE LEARNING OUTCOMES OF CLASS XI MIA MAN 4 BONE STUDENTS (STUDY ON ACID-BASE SUBJECT MATTER) - Perlawanan, Andi Tahta; Jusniar, Jusniar; Madjid, Ahmad Fudail (UNESA Journal of Chemical Education, 2022)
The purpose of this study was to determine the effect of Nearpod interactive media on discovering a learning model on learning outcomes of class XI MIA students of MAN 4 Bone. The research method used was a quasi-experimental with a quantitative approach and using a posttestonly control group design. The research population were all from class XI MIA with a total of 2 classes. The research samples were class XI MIA 1 as the experimental class and class XI MIA 2 as the control class. The data collection technique used multiple choice tests to obtain data of learning outcomes. Data analysis was conducted using descriptive and inferential statistics. The results of statistical analysis showed that the experimental class' average learning outcomes were 75.53, higher than the control class, which was 71.28. The results of statistical analysis of learning outcomes showed that the experimental and control class data came from a homogeneous population but not normally distributed, so that the test used was the Mann-Whitney test. From data analysis, it showed Zcount (3.88) > Ztable. (1.64). Based on data analysis, it could be concluded that there was an effect of Nearpod interactive media on the discovery learning model on learning outcomes of XI MIA Students of MAN 4 Bone on acid base subject matter.